PERANAN PENDIDIKAN BAHASA INGGRIS TERHADAP PROSES PEMBELAJARAN AKUNTANSI (Studi Kasus di D3 Akuntansi Universitas Pamulang) - Arifin Arifin (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2017)
ABSTRACTThis research aimed to improve English language teaching materials on an accounting program through the role of educational English language to the learning process of accounting required by accounting students at university level. Teachingmaterials used previously is to use common English materials that do not have relevance of the accounting program. This research is done on accounting courses at Pamulang universities by conducting interviews and giving a questionnaire consisting of two indicators. Targetthe needs of English language learning materials. Theresults of the study showed that students of accounting courses require special English language program that suits them. Whilethe English language skills that need to be combined with accounting programs, especially those related to the financial report writing.